Produkt turystyki wiejskiej Dolnego Śląska na konkurencyjnym rynku turystycznym okolic Wrocławia - Kutkowska, Barbara (Rural Tourism Product of Lower Silesia on the Competitive Tourist Market of Wroclaw Region, 2006)
In 2004 16 agritourist farms located nearby Wroclaw agglomeration were taken under investigation. The aim of this research is analysis of rural tourism product of this region and its methods of promotion and distribution. Moreover, the analysis of competition among agritourist farms and other tourist objects located in the closest region is the purpose of this research. Analysis of the neighborhood of the farms under investigation confirms strong competition. These areas are characterized by well-developed tourist infrastructure. There are hotels, inns, boarding-houses, centers of rest and recreation. This is the reason that agritourist farms holders must create an original offer relying on attraction of rural areas and farm stocks addressed to a specific group of buyers.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1118, t. 1, s. 525-530